2020
DOI: 10.3390/ijerph17145067
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality during COVID-19 in Four Megacities: Lessons and Challenges for Public Health

Abstract: The study described in this manuscript analyzed the effects of quarantine and social distancing policies implemented due to the Coronavirus Disease 2019 (COVID-19) pandemic on air pollution levels in four western megacities: São Paulo in Brazil; Paris in France; and Los Angeles and New York in the United States. The study investigated the levels of four air pollutants—Carbon monoxide (CO), Ozone (O3), Fine Particulate (PM2.5) and Nitrogen dioxide (NO2)—during the month of March 2020, compared to 2015–2019, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
54
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 24 publications
11
54
2
Order By: Relevance
“…The average CO levels decreased during the partial lockdown by −46.20%, and the area monitored by the AQ-IoT-6 station recorded a decrease of -50.31% in the same period ( Figure 6 ). However, the CO values are high compared to the values reported in the recent literature ( Connerton et al, 2020 ; Nakada and Urban, 2020 ;); we observed that the primary source of CO emission is motor vehicles (86%) because a non-emission vehicle pollutant verification standard has not been implemented by the State Government. Figure 6 shows the decrease in CO in the air during the twelve weeks after lockdown, a notable decrease in the concentration of several pollutants is identified between the fourth and sixth week of the study (from March 14 to 28).…”
Section: Resultscontrasting
confidence: 60%
“…The average CO levels decreased during the partial lockdown by −46.20%, and the area monitored by the AQ-IoT-6 station recorded a decrease of -50.31% in the same period ( Figure 6 ). However, the CO values are high compared to the values reported in the recent literature ( Connerton et al, 2020 ; Nakada and Urban, 2020 ;); we observed that the primary source of CO emission is motor vehicles (86%) because a non-emission vehicle pollutant verification standard has not been implemented by the State Government. Figure 6 shows the decrease in CO in the air during the twelve weeks after lockdown, a notable decrease in the concentration of several pollutants is identified between the fourth and sixth week of the study (from March 14 to 28).…”
Section: Resultscontrasting
confidence: 60%
“…Comparable PM 2.5 reductions were registered in Shanghai (−27%) by Shakoor et al. (2020) , Paris (−28%) by Connerton et al. (2020) , and New York (−29%) by Chen et al.…”
Section: Discussionmentioning
confidence: 83%
“…Comparable O 3 increases were registered by Chen et al. (2020) in NewYork (8%) and Las Vegas (17%), as well as by Connerton et al. (2020) in Paris, France (12%) and São Paulo, Brazil (30%).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One can hypothesize that less vigorous physical exertion or reduced physiological stress during a lockdown can result in fewer coronary plaque ruptures [15]. Furthermore, changes in the environment may play a role in a lower incidence of cardiovascular morbidity and mortality, since the COVID-19 lockdown has been associated with a dramatic decline in air pollution [16,17]. A reduced exposure to such air pollution due to less tra c and industrial activities during a lockdown, may lead to fewer cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%